Reference values for selected hematological, biochemical and physiological parameters of Sprague‐Dawley rats at the Animal House, Faculty of Medicine, University of Colombo, Sri Lanka - Delwatta, S.L.; Gunatilake, M.; Baumans, V.; Seneviratne, M.D.; Dissanayaka, M.L.B.; Batagoda, S.S.; Udagedara, A.H.; Walpola, P.B. (Wiley-Blackwell, 2018)
Background: Lack of available reference values in a research setting under local condi-tions can be a drawback for beginners, as the accuracy of data from control samplescannot be checked at the beginning of a research project. This affects comparisonswith data from test samples. To avoid these complications in their research projects,beginners tend to have a greater number of animals in the control group compared totest groups in order to have control group measurements within 2 SDs of the mean. Methods: As non-availability of reference values was a long‐felt need, the describedproject was conducted in order to establish a reference database for selected haematolo-gical, biochemical and physiological parameters using apparently healthy Sprague‐Dawleyrats bred in the Animal House of Faculty of Medicine, University of Colombo (UCFM).Results: Differences in mean values of packed cell volume (PCV), mean corpuscularvolume (MCV) and mean corpuscular hemoglobin concentration (MCHC), serum cre-atinine and blood glucose levels between the two genders were statistically signifi-cant. Lipid profile measurements did not differ significantly between genders, butmean and median values of triglycerides (TG) between male and female rats showeda difference of more than 10 mg/dL. The liver enzymes alkaline phosphatase (AP)and aspartate aminotransferase (AST) were also statistically significantly differentbetween sexes. Despite wide variation in mean alanine aminotransferase (ALT)between sexes, the difference was not statistically significant.Conclusion: The findings of this project should support to a certain extent the“Reduction” aspect of the 3Rs concept of Russell and Burch by reducing the numberof Sprague‐Dawley rats used in future research projects at UCFM.
Keywords: S3Rs concept; reference values; Sprague-Dawley; rat